Laboratory Evaluation of Underwater Acoustic Attenuation Provided by Air Bubble Curtains - Yori, Alfio; Barros, Jose Luis; Torres, Rodrigo; Figueroa, Felipe (Archives of Acoustics, 2026)
Air bubble curtains are widely used in Chilean salmon farming to protect fish from water pollutants. Due to new requirements from the Environmental Assessment Service, their use for underwater noise mitigation has become very important. This study aimed to evaluate the acoustic attenuation provided by a type of curtain widely used in salmon farming and seawater desalination under laboratory conditions, obtaining results independent of the conditions encountered in field work. This allowed for comparative measurements of different bubble curtain configurations. This study presents the results of an acoustic evaluation of underwater sound attenuation provided by different bubble curtain configurations, conducted in the test channel of the EngineeringDepartment at the Universidad Austral de Chile. The parameter evaluated was the insertion loss (IL). It was found that the evaluated bubble curtains provided a broadband insertion loss between 11 dB and 12 dB in the simplest configuration and IL per third-octave band equal to or greater than 10 dB. The 10 dB attenuation in the source level represents a significant reduction in the area of acoustic impact, reducing the physiological damage distances for the marine mammal species considered by at least 78.4 %.